Japan library : (Japan Publishing Industry Foundation for Culture (JPIC), 2020)
Japan library is a collection of specially selected Japanese works in English, providing a broad range of titles from the vast canon of nonfiction-politics, foreign policy, social science, culture, philosophy, science and technology, and more.